Neighborhood frequency effects in simple and complex span: Do high-frequency neighbors help or hurt? - MacMillan, Molly B.; Neath, Ian; Roodenrys, Steven (Memory & Cognition, 2024)
A word's orthographic neighborhood is the set of words that differ from the target word by one letter. Both Roodenrys (2009) and Robert et al. (Journal of Psycholinguistic Research, 44, 119-125, 2015) posit that orthographic neighbors are activated when the target word is encountered in tasks such as simple and complex span. The two accounts differ in that the former predicts a beneficial effect of this activation, because it produces feedback activation that helps redintegrate the target word, whereas the latter predicts a detrimental effect, because the need to overcome the greater interference from the larger number of higher-frequency items reduces the processing resources available. Four experiments assess the predictions of these two accounts. Experiments 1 and 2 found a beneficial effect of having a higher- compared with a lower-frequency neighborhood in both a simple and a complex span task. Experiments 3 and 4 found no detrimental effect of having one or more neighbors with higher frequency than the target in both a simple and complex span task. Implications for the two theories are discussed.